Full atomistic mechanism study of hydrogen evolution reaction on Pt surfaces at universal pHs: Ab initio simulations at electrochemical interfaces. (1st September 2022) - Qin, Xueping; Zhu, Shangqian; Wang, Yian; Pan, Ding; Shao, Minhua
Abstract: Hydrogen evolution reaction (HER) plays an indispensable role in realizing the hydrogen economy. Regardless of great efforts devoted to investigating its reaction mechanism, no unified conclusion has been reached to explain the pH-dependent kinetics. In this study, a full atomistic Pt(111)/water interfacial model is constructed where pH-dependent behaviors of HER, including Pt-H vibrations, hydrogen binding energy (HBE), and reaction kinetics are examined. In good accordance to previous experimental results, weaker HBE and Pt-H vibration are observed as pH increases. The thermodynamic and kinetic simulations of HER at Pt(111)/water interfaces indicate that HER in acidic media follows the Volmer-Tafel/Heyrovsky pathway with the second step being the rate-determining step (RDS), while it proceeds via the Volmer-Tafel pathway with water dissociation being the RDS in alkaline. The different proton sources and surface properties in acid and alkaline solutions alter HBEs and reaction pathways as well as activation energy barriers. Our full atomistic simulation mimics the electrochemical interface effectively and provides adequate understandings of HER mechanisms at universal pHs, which can be extended into studying other electrochemical reactions. Graphical abstract: Image, graphical abstract